Memonitor Kualitas Air Kolam Ikan Nila Berbasis Internet Of Things di Desa Bugel, Padarincang, Serang, Banten - Kristiyanto, Arip; Suryadi, Asep; Romansyah, Andi; Madani, Natasya Insanu; Supiah, Raihan Azzahra (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
The Ministry of Marine Affairs and Fisheries (KKP) noted that Indonesia produced 401,767 tons of tilapia in the second quarter of 2022. Water quality is a key factor in the success of tilapia aquaculture. In tilapia farming, there are several challenges, such as diseases caused by poor water quality. However, not all farmers understand water quality management. Our activity aims to implement an internet of things-based water quality monitoring system for ponds based on temperature and pH. The implementation method of this service starts from surveying, system development, testing, implementation, and evaluation. The result of this activity is the completion of a tilapia pond water quality monitoring system, with input parameters of temperature sensor (ds18d20) and pH sensor (dfrobot sen0161), NodeMCU as a processor, and monitoring using ThingsBoard. This monitoring system can be viewed through the ThingsBoard dashboard website, allowing farmers to see real-time water quality conditions.